Islam Aboge Between Heritage Tradition and Religious Sect in the Horseshoe Area - Ja'far, Suhermanto; Yaqin, Haqqul; Febriansyah, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article investigates the acculturation of Islam with the Aboge community and addresses two primary issues: firstly, the position of Islam Aboge between traditional heritage and a religious sect; and secondly, its adaptation in the face of changing times. The research employs a qualitative methodology with field research as the primary approach. Data collection techniques include interviews, observations, and document analysis, while data analysis involves thematic analysis to identify patterns and themes in the integration of Islam and Aboge traditions. The findings reveal that Islam Aboge, as a hereditary tradition, remains prevalent among local communities in East Java, particularly in Probolinggo and Jember, where it is embraced by many ethnic Madurese. This cultural interaction has enabled the Islam Aboge community to coexist with mainstream Islamic society. While Islam Aboge shows some similarities with the Abangan typology in Clifford Geertz’s framework, the community retains fundamental Islamic practices such as prayer and fasting, maintaining a distinct religious identity. However, the community faces challenges from modernization, having led to a gradual shift toward mainstream Islam and a decline in adherence to Aboge traditions. This study contributes to the understanding of Islamic acculturation in local contexts and the dynamics of religious identity in the face of social change. It highlights the complexities of maintaining traditional religious practices within modern societal structures. The findings provide valuable insights into the interaction between religion and culture, enriching discussions on religious pluralism and heritage preservation